2021
DOI: 10.1021/acscatal.1c02564
|View full text |Cite
|
Sign up to set email alerts
|

Heck-Type Coupling of Fused Bicyclic Vinylcyclopropanes: Synthesis of 1,2-Dihydropyridines, 2,3-Dihydro-1H-azepines, 1,4-Cyclohexadienes, and 2H-Pyrans

Abstract: Herein, we report a versatile approach for the endocyclic ring opening of bicyclic vinylcyclopropanes triggered by Heck arylations. The key step for this transformation is a β-C-elimination allowing the ring expansion of cyclopropanated pyrroles, piperidines, furans, as well as cyclopentadienes to grant access to the corresponding 1,2-dihydropyridines, 2H-pyrans, 2,3-dihydro-1H-azepines, and 1,4-cyclohexadienes, respectively. Additionally, gem-disubstituted cyclopropanated furans showed unexpected behavior by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 114 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Among all possible strategies to reach these structures, the inherent strain of polysubstituted cyclopropanes could serve as a central platform for selective ring-opening of three-membered rings toward the formation of these desired acyclic motifs. , In this context, we have recently reported several modular and stereodivergent strategies to construct congested acyclic molecular frameworks that bear several stereogenic centers at different positions with remarkably high levels of stereocontrol (Scheme b). Notably, using these strategies, the enantioselective preparation of the natural product botryococcene and its epimer as well as the diastereoselective preparation of the side chain of α-tocopherol could be easily and efficiently achieved in a few catalytic steps from commercially available starting materials. Interestingly, the selectivity of the ring-opening is usually dictated by either the presence of an electron-withdrawing group, , a leaving group ,,, that polarizes a specific σ bond through a “push–pull” effect, by constraints of a bicyclic system (Scheme , equations 1b 2 and 1b 5 ), or by the formation of the less substituted and more stable primary alkyl metal intermediate ,, (Scheme , equation 1b 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among all possible strategies to reach these structures, the inherent strain of polysubstituted cyclopropanes could serve as a central platform for selective ring-opening of three-membered rings toward the formation of these desired acyclic motifs. , In this context, we have recently reported several modular and stereodivergent strategies to construct congested acyclic molecular frameworks that bear several stereogenic centers at different positions with remarkably high levels of stereocontrol (Scheme b). Notably, using these strategies, the enantioselective preparation of the natural product botryococcene and its epimer as well as the diastereoselective preparation of the side chain of α-tocopherol could be easily and efficiently achieved in a few catalytic steps from commercially available starting materials. Interestingly, the selectivity of the ring-opening is usually dictated by either the presence of an electron-withdrawing group, , a leaving group ,,, that polarizes a specific σ bond through a “push–pull” effect, by constraints of a bicyclic system (Scheme , equations 1b 2 and 1b 5 ), or by the formation of the less substituted and more stable primary alkyl metal intermediate ,, (Scheme , equation 1b 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the stability issues of diazo compounds and challenges associated with the low regioselectivity of the product, it has been vastly used by researchers for the synthesis of ring expansion and chain elongation through appropriate substitution patterns in the starting ketone substrate. Alternatively, ring-expanded enones have also been prepared by the rearrangement of protected 1-alkenyl-1-cycloalkanols mediated by Ti­(III), Pd­(II), and Hg­(II) . Radical-based ring expansion reactions, proceeding via the alkoxy-radical fragmentation of strained three- or four-membered rings, are also quite well studied .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, monocyclopropanated heterocycles 7 , representing donor–acceptor substituted cyclopropanes, have been proven to undergo the chemo-, regio-, and stereoselective cleavage of the exocyclic cyclopropane bond, enabling various synthetic transformations such as rearrangements or ring-opening with nucleophiles and electrophiles. In contrast, the selective cleavage of the endocyclic cyclopropane bond in 7 , which would result in the ring-expansion to piperidines or pyrans, remains a highly underexplored topic with only few examples reported. ,, By extension, a carbocyclic analogue would provide stereoselective access to substituted cyclohexenes. We questioned if the inherent donor–acceptor electron flow in 7 can be reversed by generating an electron-deficient center at its C4 postion. In earlier work, we found that the radical intermediate 8 (X = NBoc) still results exclusively in the ring-opening of the exocyclic cyclopropane bond (Figure ).…”
Section: Introductionmentioning
confidence: 99%